209k views
2 votes
(3y + 2)(7y) y= 1
How do I evaluate that. Please show work

2 Answers

6 votes

Answer:

1. y = 1/7 = 0.143

2. y = 2/3 = 0.667

Explanation:

STEP 1 :

Equation at the end of step 1

(3y - 2) • (7y - 1) = 0

STEP 2 :

Theory - Roots of a product

2.1 A product of several terms equals zero.

When a product of two or more terms equals zero, then at least one of the terms must be zero.

We shall now solve each term = 0 separately

In other words, we are going to solve as many equations as there are terms in the product

Any solution of term = 0 solves product = 0 as well.

Solving a Single Variable Equation:

2.2 Solve : 3y-2 = 0

Add 2 to both sides of the equation :

3y = 2

Divide both sides of the equation by 3:

y = 2/3 = 0.667

Solving a Single Variable Equation:

2.3 Solve : 7y-1 = 0

Add 1 to both sides of the equation :

7y = 1

Divide both sides of the equation by 7:

y = 1/7 = 0.143

User Rewritten
by
5.1k points
4 votes

Answer: 17

Explanation:

y= 1

(3y + 2)(7y)

(3(1) + 2(7(1)) Replace y with given number

(3 + 2(7)) Multiply 1 to 3 and 7

(3 + 14) Multiply 2 and 7

(17) Add 3 and 14

User Vlad Dobrydin
by
4.8k points